Basic motor competencies of kindergarten children: Differences in sex, age, sport club membership, and physical activity in everyday life - Melina Walter; Lucas Schole; Wiebke Langer; Erin Gerlach (Bern Open Publishing, 2024)
Introduction The kindergarten age (four to six years) is considered to be a central phase of motor development, as basic motor competencies (BMC) are formed here. The development of BMC is crucial for participating in physical activities (PA) and sport, which in turn supports the development of a healthy lifestyle. Two domains of competence can be distinguished: the competence domain of object-movement includes tasks related to handling balls and the competence domain of self-movement includes movements of one's own body (Herrmann et al., 2022). Methods The BMC of N = 44 children (aged M = 58.1 months, SD = 7.9, 54.5% boys) were assessed in Hamburg, Germany, using the MOBAK-KG instrument (Herrmann et al., 2020). The children's sport club membership and PA were recorded from the parents' questionnaire. Data was analyzed using t-tests. Results Boys achieved higher scores in object-movement (p = .047, d = .62), whereas there were no significant differences between boys and girls in self-movement. Older children (60-67 months) performed significantly better in both domains (self-movement: p = .024, d = .72; object-movement: p < .001, d = 1.48) than the younger cohort (39-59 months). More than half of the children are physically active for at least half an hour on three days or less per week. Children who engage in PA for at least half an hour on four or more days a week achieved significantly better results in self-movement (p = .025, d = .72) but not in object-movement. Significant differences were also found between BMC and sport club membership in both domains (self-movement: p = .009, d = .84; object-movement: p = .004, d = .94) in favor of the children who are members of a sport club, with boys being in sport clubs more often than girls. Discussion/Conclusion A high level of BMC seems to enable children to take part in sports activities even in the kindergarten age. Boys already showed higher performance in handling balls in that age. The higher scores in both domains in favor of the older cohort indicate that the BMC of kindergarten children must always be interpreted in an age-specific manner. PA can be seen as an important factor in promoting self-movement. However, it should be noted that the information on PA is based on the subjective assessments of the parents, who might be biased. Participation in sport clubs is, however, relatively selective and depends on various factors, such as the social environment. Therefore, it is important to provide PA time in kindergarten. This study is the first in Germany which reproduces results from the Swiss context and refers to the validity of the MOBAK-KG instrument across cultures. References Herrmann, C., Bretz, K., Kühnis, J., Seelig, H., Keller, R., Storni, S., Voisard, N., Rossi, F., & Ferrari, I. (2022). Monitoring motorischer Basiskompetenzen von Kindergartenkindern in der Schweiz. Abschlussbericht MOBAK-Monitoring 2021 [Monitoring the basic motor skills of kindergarten children in Switzerland. Final report MOBAK-Monitoring 2021] Zürich: Pädagogische Hochschule Zürich. https://doi.org/10.5281/zenodo.6380396 Herrmann, C., Ferrari, I., Wälti, M., Wacker, S., & Kühnis, J. (2020). MOBAK-KG: Motorische Basiskompetenzen im Kindergarten. Testmanual [MOBAK-KG: Basic motor skills in kindergarten. Test manual] (3rd ed.). https://doi.org/10.5281/zenodo.3774435